Linagliptin Attenuates the Cardiac Dysfunction Associated With Experimental Sepsis in Mice With Pre-existing Type 2 Diabetes by Inhibiting NF-κB - Al Zoubi, Sura; Chen, Jianmin; Murphy, Catherine; Martin, Lukas; Chiazza, Fausto; Collotta, Debora; Yaqoob, Muhammad M.; Collino, Massimo; Thiemermann, Christoph (Frontiers in Immunology, 2018)
The mortality rate of patients who develop sepsis-related cardiac dysfunction is high. Many disease conditions (e.g. diabetes) increase the susceptibility to infections and subsequently sepsis. Activation of the NF-κB pathway plays a crucial role in the pathophysiology of sepsis-associated cardiac dysfunction and diabetic cardiomyopathy. The effect of diabetes on outcomes in patients with sepsis is still highly controversial. We here hypothesized that type 2 diabetes (T2DM) augments the cardiac (organ) dysfunction associated with sepsis, and that inhibition of the NF-κB pathway with linagliptin attenuates the cardiac (organ) dysfunction in mice with T2DM/sepsis. To investigate this, 10-week old male C57BL/6 mice were randomised to receive normal chow or high fat diet (HFD), 60% of calories derived from fat). After 12 weeks, mice were subjected to sham surgery or cecal ligation and puncture (CLP) for 24 hours. At 1 hour after surgery, mice were treated with linagliptin (10mg/kg, i.v.), IKK-16 (1mg/kg, i.v.) or vehicle (2% DMSO, 3ml/kg, i.v.). Mice also received analgesia, fluids and antibiotics at 6 and 18 hours after surgery. Mice that received HFD showed a significant increase in body weight, impairment in glucose tolerance, reduction in ejection fraction (%EF) and increase in alanine aminotransferase (ALT). Mice on HFD subjected to CLP showed further reduction in %EF, increase in ALT, developed acute kidney dysfunction and lung injury. They also showed significant increase in NF-κB pathway, iNOS expression and serum inflammatory cytokines compared to sham surgery group. Treatment of HFD-CLP mice with linagliptin or IKK-16 resulted in significant reductions in i) cardiac, liver, kidney and lung injury associated with CLP-sepsis, ii) NF-κB activation and iNOS expression in the heart and iii) serum inflammatory cytokine levels compared to HFD-CLP mice treated with vehicle. Our data show that pre-existing type 2 diabetes phenotype worsens the organ dysfunction/injury associated with CLP-sepsis in mice. Most notably, inhibition of NF-κB reduces the organ dysfunction/injury associated with sepsis in mice with pre-existing T2DM.